6 and 10 are part of the 2 table so you would have 2(3x-5) thats the farthest we can factor it down :)
Step-by-step explanation:
4.2y=23.7
y=5.642857
YAYYYYYYYYYYYYYYYYYYY
Answer: 5x(x-1)
Step-by-step explanation:
2(x2 - x) + 3 (x2 - x)
5x(2 power) - 5x
= 5x(x - 1)
Answer:
Step-by-step explanation:
x³-6x²+11x-6
put x=1
1³-6×1²+11×1-6=1-6=11-6=0
by synthetic division
1| 1 -6 11 -6
| 1 -5 6
|----------------
| 1 -5 6 |0
x²-5x+6=0
x²-2x-3x+6=0
x(x-2)-3(x-2)=0
(x-2)(x-3)=0
x=1
x-1=0
so x³-6x²+11x-6=(x-1)(x-2)(x-3)